2018
DOI: 10.1021/acs.jpcc.7b09717
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Anisotropic Thermal Conductivity and Elastic Properties in Intercalated Graphite via Lithium Ions

Abstract: The electrochemical intercalation of metal ions into layered materials is a useful strategy to reversibly tune thermal-transport properties, but the fundamental mechanisms are not well understood. In this study, we systematically investigated the effects of lithium-ion concentrations on the anisotropic thermal conductivity of intercalated graphite by molecular-dynamics simulations and a continuum-mechanics method. It was found that the in-plane thermal conductivity rapidly decreased to 34.3% of that of graphit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
1
17
0
1
Order By: Relevance
“…Similarly, the in-plane κ for bulk MoS 2 ranges from 85-112 Wm -1 K -1 [9,10], [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] times higher than the cross-plane values [11]. These weakly bonded structures provide avenues for tuning κ by varying layer number [9], applying strain [12,13] and intercalating atoms between layers [14][15][16].…”
mentioning
confidence: 99%
“…Similarly, the in-plane κ for bulk MoS 2 ranges from 85-112 Wm -1 K -1 [9,10], [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] times higher than the cross-plane values [11]. These weakly bonded structures provide avenues for tuning κ by varying layer number [9], applying strain [12,13] and intercalating atoms between layers [14][15][16].…”
mentioning
confidence: 99%
“…This phenomenon has been theoretically and experimentally investigated in various materials for the purpose of tuning thermal conductivity. [21][22][23][24][25][26] Here, focus will be given to previous studies of common electrode materials used in LIBs, i.e., lithium-intercalated graphite (Li x C 6 ) 21,22 and lithium-intercalated layered transition-metal oxides (Li x TMO 2 ), 23 especially Li x CoO 2 . 26 Prior molecular dynamics (MD) simulations predicted an anisotropic effect of lithium intercalation on the thermal conductivity of Li x C 6 , i.e., the in-plane k decreases monotonically with the degree of lithiation, whereas the through-plane k decreases first and then increases with the amount of intercalated Li + ions.…”
Section: Resultsmentioning
confidence: 99%
“…Another signal not exploited by the electrochemical community is the variation of thermal conductivity related to electrochemically induced structure/phase transitions. [21][22][23][24][25][26][27] Specifically, previous studies of lithium cobalt oxide 23,26 and graphite 21,22 demonstrated the dependence of the thermal conductivity of electrode materials on the degree of lithiation/delithiation. This suggests the possibility of determining the lithium concentration distribution in battery electrodes by spatially mapping their thermal conductivity.…”
Section: Context and Scalementioning
confidence: 99%
“…Intercalation offers an effective methodology to tailor the thermal conductivity of 2D materials by changing the structural and compositional disorder, including changes in layer spacing, interaction strengths between adjacent layers and phase transitions. [ 78–83 ] Experimentally, there are a number of studies to reveal the effect of intercalation on thermal conductivity of 2D layered materials. As described above, the amounts of intercalated ions can be exactly controlled via electrochemical method, enabling the investigations of how disorder affects their thermal conductivity.…”
Section: Multifunctionalities Of Intercalated Devicesmentioning
confidence: 99%